The aesthetic and artistic values of textiles in the Islamic era (Journal of the College of Basic Education, 2022)
Islamic textiles have expressed their aesthetic value and artistic originality, as well as their social, intellectual and religious significance, through the diversity of their forms, as a result of the many transformations that have taken place in Islamic societies in different parts of the world, whether plant and geometric motifs or straight and parallel lines. Not only that, but it has gone beyond that and has become a research starting point that many researchers and scholars seek in Islamic and heritage affairs, and based on these principles, the researcher found the necessity to delve into the aesthetic and artistic values ​​in the manufacture of the Islamic fabric and to reveal its intellectual and expressive implications